2012
DOI: 10.1007/s12603-012-0404-6
|View full text |Cite
|
Sign up to set email alerts
|

Life dissatisfaction and eating behaviors among older African Americans: The protective role of social support

Abstract: Objectives To examine (a) the influences of life dissatisfaction and dietary social support on eating behaviors (a high-fat diet and fruit/vegetable consumption) of older African Americans and (b) the moderating role of perceived dietary social support on the association between their life dissatisfaction and unhealthy eating behaviors. Design Baseline data from a larger intervention study of mid-life and older African Americans. The study incorporated a quasi-experimental design with random selection of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…psychological competency and vulnerability) in their older years. Thus, the current findings of direct additive effects involving these psychological processes may be another example of the harmful influence of chronic stress on health-promoting behaviors of older African Americans (Wickrama et al, 2012b). …”
Section: Discussionmentioning
confidence: 87%
“…psychological competency and vulnerability) in their older years. Thus, the current findings of direct additive effects involving these psychological processes may be another example of the harmful influence of chronic stress on health-promoting behaviors of older African Americans (Wickrama et al, 2012b). …”
Section: Discussionmentioning
confidence: 87%
“…Povey and colleagues' (2000) and Armitage and Conner's (1999) Wickrama et al (2012) found social support to be a significant moderator in regards to healthy eating, among college students and older Black samples, respectively. In this study neither perceived family social support nor friend social support moderated the effect of gender, BMI, income adequacy, and religious commitment on DFI.…”
Section: Research Questionmentioning
confidence: 98%
“…In the food security studies there were mixed findings regarding whether social support was a significant moderator (Muzoora, Martin, & Weiser, 2012;De Marco & Thorburn, 2009). Social support was a significant moderator in the studies regarding eating behaviors and healthy eating (McKinley, 2009;Wickrama et al, 2012).…”
Section: Modifying and Mediating Factors Of Dfimentioning
confidence: 99%
“…93 Diets endorsed primarily on the basis of medical attributes might not be easily initiated or sustained for many patients who would benefit, because the perception that foods have health benefits might simultaneously generate the perception that they are unappealing. Advertising and cultural norms that elevate the allures of tobacco and alcohol to people of diverse cultural backgrounds can have an impact that is not apparent to the clinician.…”
Section: Special Considerationsmentioning
confidence: 99%